The Empire Strikes Back? Media Freedom Public Interest and Neoliberalism in the Aftermath of the Eurozone Economic Crisis - Figueiras, Rita (Javnost-The Public, 2022)
The article explores articulations between capital, the state, and the media by taking Angola and Portugal as the empirical context to examine specific relations between neoliberal and state influence against media democracy normativity in the aftermath of the Eurozone economic crisis. This includes questioning the neoliberal narrative of capital both as a hegemonic force that disempowers nation states and homogenises national media configurations. In order to do it, the “Angolanisation” of the Portuguese economy will be addressed to, then, look at the role of the Portuguese media in consolidating Angola's position within Portuguese society. It is argued that Portuguese media defined their basic commitment as promoters of Angolan interests and together with other institutions they were part of a larger system that worked as internal colonisation agents. The article contends a more differentiated perspective on neoliberalism and offers arguments to move media democratic theories beyond its normativity in the field of media studies by looking at neoliberalism as a context sensitive concept and at the media as an expression of specific relations between neoliberal and state influence in articulation with other logics. In the case in point, Portugal's peripheral condition and colonial heritage.